This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Suppose ∣ f ( x ) ∣ − ∣ g ( x ) ∣ + ∣ h ( x ) ∣ = F ( x )
And since x = − 1 and x = 0 are critical points of F ( x ) we can write it as
F ( x ) = a ∣ x + 1 ∣ + b ∣ x ∣ + c x + d , where a , b , c , d are constants.
F ( x ) = ⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ ( c − a − b ) x + d − a , x < − 1 ( a + c − b ) x + a + d , − 1 ≤ x ≤ 0 ( a + b + c ) x + a + d , x ≥ 0
On comparing with the given we get a = 2 3 , b = 2 − 5 , c = − 1 , d = 2 1
This gives f ( x ) = 2 3 x + 3 , g ( x ) = 2 5 x , h ( x ) = − x + 2 1
Note that by symmetry f ( x ) and h ( x ) may be interchanged
And finally g ( 2 ) = 5